Iron(III) edta-accelerated growth of gold/silver core/shell nanoparticles for wide-range colorimetric detection of hydrogen peroxide - Mahdi Hemmati; Amir Hossein Q. Selakjan; Forough Ghasemi (Scientific Reports)
Abstract As a naturally occurring reducing and oxidizing agent, hydrogen peroxide (H2O2) has a role in several biotic and abiotic processes. Hence, the onsite, precise, and rapid determination of H2O2 is crucial. Herein, we propose a method for colorimetric detection of H2O2 on the basis of hindered formation of gold/silver core/shell nanoparticles. We used ascorbic acid (AA) as the electron donor to reduce silver ions (Ag+) to be shelled around gold nanoparticles and iron(III) edta as an accelerator reactant. Upon reduction of Ag+, owing to the formation of core/shell nanoparticles, the color of the system changes from pink to yellow/orange in the spherical nanoparticles and from pink to purple/blue/green/yellow/orange in the nanorods. The nanorods distinguished color in a rainbow manner for higher concentrations of H2O2, and spherical nanoparticles were critical in the sensitive detection of lower concentrations of H2O2. H2O2 scavenges AA electrons and therefore inhibits core/shell formation and, consequently, restrains the system’s spectral shift and color change. This characteristic was exploited to measure different concentrations of H2O2. Under well-optimized conditions, various concentrations of H2O2 ranging from 1.0 to 50 µΜ have shown an acceptable linear relationship with different colors and, with a limit of detection (LOD) of 230 nM. Furthermore, various real samples were examined to confirm the practicality of our developed probe.